The cartels : the story of Mexico's most dangerous criminal organizations and their impact on U.S. security - Grayson, George W., 1938- (Santa Barbara, California : Praeger, an imprint of ABC-CLIO, LLC, 2014)
"An up-to-date examination of Mexico's version of the "War on Drugs" that exposes the evolution of major cartels and their corruption of politicians, law-enforcement agencies, and the Army"--
Introduction -- The ten commandments and "EI Padrino" -- The United States seeks interdiction of drugs from Colombia -- Shift in
Includes bibliographical references (p. 299-303) and index.
Keywords: Drug traffic -- Mexico; Drug traffic -- Government policy -- Mexico; Organized crime -- Mexico; Cartels -- Mexico; Corruption -- Mexico; HISTORY / Latin America / Mexico; SOCIAL SCIENCE / Criminology; Cartels; Corruption; Drug traffic; Drug traffic -- Government policy; Organized crime; Mexico